Piezo devices using poly(vinylidene fluoride)/reduced graphene oxide hybrid for energy harvesting - Kumar C.; Gaur A.; Rai S.K.; Maiti P. (My University, 2025)
Harvesting of energy, the continuous human effort throughout history, or reclaim energy from mechanical stress is presented in this work. Reduced graphene oxide, homogeneously dispersed in poly(vinylidene fluoride), induces the electroactive phases in the polar polymer. Good dispersion arising from better interactions between 2-D nanofiller and polymer chain is revealed through transmission electron microscopy and spectroscopic measurement. The induction of electroactive phases in polymer in the presence of nanofiller has been confirmed through structural, spectroscopy and thermal studies. Electroactive phases is confirmed through FTIR peaks at 840 cm−1 for β∕γ phase and 884 cm−1 band for γ-peak in nanohybrid against 796, 876 and 975 cm−1 absorption peaks for α-phase in pure PVDF. Morphological alteration (both surface and bulk) reaffirms the change of phases in the nanohybrid vis-à-vis pure polymer. Quantification of different phases has been made, in the presence of varying content of graphene, which is directly reflected in their properties. Greater mechanical and thermal stability of the nanohybrid help promoting this class of hybrid material for device application. Devices have been fabricated to understand the piezoelectric responses from the hybrid materials and output electrical signals (both voltage and current) are measured under mechanical stress applied from a motor driven mechanical setup. Both output voltage and current significantly increase either with greater applied load or graphene content in hybrid primarily due to higher strain produce or better induction of piezo phase, respectively. Moderately high electrical power density up to 14 μW/cm3 is measured from the device made of the hybrid material, suitable for a number of low power consuming electronic self-power devices and wireless sensors. © 2017 Elsevier B.V.